Development of a Csy4-Processing TRV-Based CRISPR/Cas9 Genome Editing System in Nicotiana benthamiana - Yanjie Luo; Xiaodong Tang; Cuihong Yu; Yang Qiu; Julia S. Nowak; Qing Shi Lu; Lining Tian; Ren Na (Plant Molecular Biology Reporter, 2024)
The CRISPR/Cas9 system is a site-specific genome editing tool that has been widely used in various plant species. The plant virus-based gRNA (guide RNA) delivery system, which differs from the typical Agrobacterium -mediated transformation, is an attractive method to facilitate the application of CRISPR/Cas9. The virally delivered gRNA is usually driven by heterologous plant U6 or viral promoters (e.g., pea early-browning virus, PEBV; barley stripe mosaic virus, BSMV). However, heterologous promoters may have poor performance in some cases. In this paper, a feasible option to detach gRNA(s) from the virus genome is employed. Specifically, the Csy4-RNA processing system is used to release gRNA(s) from the tobacco rattle virus (TRV). The coding sequences of Cas9 and Csy4 nucleases are cloned into a single polycistronic expression cassette under an estrogen-inducible promoter in a binary vector, and the gRNA is cloned into the TRV genome flanked by two 20 bp Csy4 recognition sites. The results show that the Csy4-processing TRV-based delivery system works effectively in targeting single and multiple sites, nucleotide replacement, and large fragment deletion in Cas9-mediated genome editing via transient expression in Nicotiana benthamiana . The Csy4-TRV is a promising gRNA(s) processing and delivery system for CRISPR/Cas9 genome editing. This method can be easily adapted to other plant RNA viruses, facilitating the application of the CRISPR/Cas9 system in plants.